Ion range measurements using fluorescent nuclear track detectors - Klimpki, Grischa; Osinga-Blättermann, Julia-Maria; Herrmann, R.; Akselrod, M. S.; Jäkel, Oliver; Greilich, Steffen (Radiation measurements, 2013)
Fluorescent nuclear track detectors (FNTDs) show excellent detection properties for heavy charged particles and have, therefore, been investigated in this study in terms of their potential for in-vivo range measurements. We irradiated FNTDs with protons as well as with C, Mg, S, Fe and Xe ion beams (3-9 MeV/u) over a broad range of fluences (4.5e5-1.0e11 cm−2) with the detectors' optical c-axis positioned perpendicular to the beam direction. All measured ion ranges (for single track as well as track bulk intensity irradiations) deviate less than 3% from tabulated SRIM data (Ziegler et al., 2009), independent of particle type, energy, fluence and linear energy transfer. Proton irradiation of detectors placed inside a polymethyl methacrylate (PMMA) phantom at the Heidelberg Ion-Beam Therapy Center showed promising results for future in-vivo FNTD applications.